Internet connectivity disruption in MK (North Macedonia) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in North Macedonia. Data sourced from IODA.
Network Disruption Incident ID: MK-2026-0008. Severity: critical. Confidence: 67%